Updated Sea Ice Products for the NIMBUS 5 Electrically Scanning Microwave Radiometer data from 1972–1977 ... - Tellefsen, Emil Haaber; Kolbe, Wiebke Margitta; Tonboe, Rasmus Tage (Technical University of Denmark, 2024)
The Electrically Scanning Microwave Radiometer (ESMR) instrument onboard the NIMBUS 5 satellite was a one-channel microwave radiometer that measured the 19.35 GHz horizontally polarized brightness temperature (TB) from 11 December 1972 to 16 May 1977.Kolbe et. al. (2024) reprocessed this data in order to derive sea Ice concentration for the period and showed that sea ice extend and concentration was indeed recoverable, but one major challenge was that the implemented one-channel algorithm was unable to distinguish first year ice and multiyear ice, resulting in ambiguity between areas with multi-year ice, and areas with low sea ice concentration. Furthermore, since publishing, we have found the applied filtering to be removing too much data, especially after 1975, and on top of that, we have resolved minor data issues.Two datesets are uploaded here, split in to 4 files ;1) A reprocessed version of the data using the methods of Kolbe et. al. (2024), but with some corrections to the output and a new filtering ...